The Influence of Customer E-Service, Information Quality, and Customer Privacy on Shopee’s Customer Loyalty with Customer Satisfaction as the Intervening Variable in Medan - Alimin, Erina; Jocelyn, Ivana (LPPM Institut Pendidikan Nusantara Global, 2024)
At present, a wide range of sectors and industries employ technology information for their operations, specifically in the area of electronic e-commerce. Shopee Pte. Ltd., operating under the trade name Shopee, is a worldwide technology corporation headquartered in Singapore that specializes in electronic commerce and Shopee emerges as the leading e-commerce platform in Indonesia during the initial quarter of 2023. However, Shopee's customer e-service, information quality, and customer privacy still has problems even though they are currently the leading e-commerce company. Researchers must therefore analyse the factors of the variables that influence customer loyalty with customer satisfaction as the intervening variable in order to endure the industry's intense competition. The sample in this study was 97 respondents .The sample itself was being collected using purposive sampling and distributed to customers that using Shopee in the last 2 years The sample itself was being collected using purposive sampling and distributed to customers that using Shopee in the last 2 years. The result of this research has shown that customer e-service, information quality, and customer privacy have a significant influence on customer loyalty with customer satisfaction as the intervening variable. Writers recommend Shopee to provide its customers with regular updates on its privacy policies, invest in customer education to educate customers on the importance of data privacy, and introducing more privacy-enhancing technology, and investing more in their employees, particularly in customer e-service